2018
DOI: 10.30574/gscbps.2018.5.2.0116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rotavirus infection in diarrheic newborn calves in Abidjan region, Ivory Coast

Abstract: The aim of the current study was to identify the prevalence of rotavirus infection in newborn calves aged from 1 day to 3 months old in Abidjan region. A total of 145 fecal samples were collected from both diarrheic (n=135) and nondiarrheic (n=10) neonatal calves. Neonatal calves' fecal samples were collected in dry seasons and in rainy seasons in Abidjan and suburbs from 2015 to 2017. Investigated calves were divided into 4 age groups (1-10 days old, 10-25 days old, 25-60 days old and ≤90 days old). All sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…Diarrhea in calves frequently occurs in newborns within the age of 1∼3 months, and several studies on calf diarrhea target less than 3 months of age (Björkman et al, 2003;Alfieri et al, 2006;Monney et al, 2018;Singh et al, 2020;Wei et al, 2021). Likewise, the results of this study showed that the proportion of diarrheic feces collected from calves less than 3 months old was 92.3% (n=2,063) of 2,234 samples with confirmed age.…”
Section: Because Diarrhea Is One Of the Most Common Diseasessupporting
confidence: 71%
See 1 more Smart Citation
“…Diarrhea in calves frequently occurs in newborns within the age of 1∼3 months, and several studies on calf diarrhea target less than 3 months of age (Björkman et al, 2003;Alfieri et al, 2006;Monney et al, 2018;Singh et al, 2020;Wei et al, 2021). Likewise, the results of this study showed that the proportion of diarrheic feces collected from calves less than 3 months old was 92.3% (n=2,063) of 2,234 samples with confirmed age.…”
Section: Because Diarrhea Is One Of the Most Common Diseasessupporting
confidence: 71%
“…Rotaviruses are known to have an age-dependent incidence. A study conducted by Monney et al, (2018) showed that the prevalence of rotavirus infection was the highest in 10∼25-day-old calves. Other studies also reported a higher occurrence of diarrhea caused by rotavirus in neonatal calves from 1 week to 2 months of age (Alfieri et al, 2006;Papp et al, 2013;Masuda et al, 2014).…”
Section: Because Diarrhea Is One Of the Most Common Diseasesmentioning
confidence: 99%
“…A total of 272 fecal samples (102 from Mbeya, 89 from (Yahaya et al, 2018), Tunisia (Fodha et al, 2005), Nigeria (Babalola et al, 20200. But also lower prevalence compared to this study have been reported in Nigeria (Garba et al, 2020), Ethiopia (Debelo et al, 2021). Also the results were comparable to other countries outside Africa such as Australia (Swiatek et al, 2010), India and Mexico (Rodrguez-Limasa et al, 2009;Basera et al, 2010).…”
Section: Prevalence and Genotypes Distribution Of Rva In Calvesmentioning
confidence: 99%
“…Only the G10 genotype was found in cattle circulating in Mbarali and Mvomero, along with untypeable P genotypes. The G10 genotype has been identified as one of the most common genotypes circulating in cattle in several African countries, including Ivory Coast, Morocco, and Nigeria (Monney et al, 2019;Babalola et al, 2020;Amine et al, 2020). The G10 reported has been linked to numerous cases of diarrhea in calves (Badaracco et al, 2013;Monney et al, 2019).…”
Section: Prevalence and Genotypes Distribution Of Rva In Calvesmentioning
confidence: 99%
See 1 more Smart Citation